TACI Isoforms Regulate Ligand Binding and Receptor Function - Garcia-Carmona, Yolanda; Ting, Adrian T.; Radigan, Lin; Athuluri Divakar, Sai Krishna; Chavez, Jose; Meffre, Eric; Cerutti, Andrea; Cunningham-Rundles, Charlotte (Frontiers in Immunology, 2018)
TACI signals activate B cell proliferation, isotype switch and antibody production in both normal immunity and autoimmune states. In contrast to murine TACI, the human TACI gene undergoes alternative splicing to produce short and long isoforms (TACI-S and TACI-L). In previous studies, we showed that transduction of the short, but not long isoform, into murine B cells or human pre-B cells lacking TACI, caused them to become transcriptional and morphologically identical to plasma cells. These data suggest that the expression of different isoforms in humans provides unique controls on B cell maturation. In these studies we show that TACI-S and TACI-L form complexes in a ligand-independent manner, not dependent on a single extracellular domain. Both TACI isoforms are detectable in the endosomal cellular compartment where they co-localize with MyD88, TRAF6 and the activated 65kDa form of TLR9, depending on a conserved intracellular TACI sequence. In contrast to TACI-L expressing cells, or cells bearing both isoforms, TACI-S binds ligands BAFF and APRIL with substantially greater affinity and promotes enhanced NF-kB activation. Using isoform-specific monoclonal antibodies, we show that while TACI-L is predominant as a surface receptor surface on human B cells, significantly more TACI-S is noted in the intracellular compartment and also in marginal zone, isotype switched and plasmablast in resting B cells. TACI-S is increased in tonsillar B cells and also in the intracellular compartment of activated peripheral B cells. These data shows that alternative splicing of the human TACI gene leads to two isoforms both of which intersect with MyD88 and TRAF6 and form complexes with TLR9, but the two isoforms have different ligand binding capacities, subcellular locations and activation capabilities.